Food Insufficiency and Mental Health in the U.S. During the COVID-19 Pandemic - Nagata, Jason M.; Ganson, Kyle T.; Whittle, Henry J.; Chu, Jonathan; Harris, Orlando O.; Tsai, Alexander C.; Weiser, Sheri D. (American journal of preventive medicine, 2021)
During the COVID-19 pandemic, the rates of food insecurity and mental illness have been projected to increase in the U.S. owing to significant social and economic disruption. This study aims to estimate the prevalence of food insufficiency (often the most extreme form of food insecurity), the correlates of food insufficiency, and the associations between food insufficiency and symptoms of poor mental health in the U.S. during the COVID-19 pandemic. Cross-sectional data from 63,674 participants of the U.S. Census Household Pulse Survey were collected and analyzed in 2020. Multiple Poisson regression models were used to estimate associations with food insufficiency. Food insufficiency rose from 8.1% to 10.0% from March to June 2020. Factors associated with food insufficiency included lower age, Black/African American or Latinx race/ethnicity, being unmarried, larger household size, recent employment loss, income below the federal poverty line, and lower education (all p<0.001). Food insufficiency was independently associated with all symptoms of poor mental health, adjusting for socioeconomic and demographic factors (adjusted RRs ranged from 1.16 to 1.42, all p<0.001). The association between food insufficiency and poor mental health was attenuated among people who received free groceries or meals. Food insufficiency has increased during the COVID-19 pandemic and affects vulnerable populations, placing individuals at higher risk for symptoms of poor mental health. Particularly in the current crisis, clinicians should regularly screen patients for food insufficiency and mental health outcomes as well as provide support in accessing appropriate resources.